Students’ perceptions towards esp course: a case study of english for accounting course at national economics university = Cảm nhận của sinh viên về khóa học tiếng anh chuyên ngành: nghiên cứu trường hợp điển hình khóa tiếng anh ngành kế toán, đại học kinh tế quốc dân - Chu, Hứa Minh Hiền (2021)
Course evaluation is one of the most important processes to ensure the quality of an entire program, and it is particularly essential in the ESP context. This study aims at exploring Accounting and Auditing majored students’ perceptions towards the English for Accounting course at National Economics University and suggest possible solutions to improve the quality of the course. To achieve these targets, a combination of quantitative and qualitative methods is used with two data collection instruments, namely questionnaire and semi-structured interview. The findings reveal that there are both strong points and weaknesses of the course regarding fulfillment of learner needs, authenticity, and fostering of learner autonomy. The results suggest certain modification being made in terms of the course duration, materials, content and teaching methodologies for future improvements.